KERENTANAN INDONESIA DARI ANCAMAN KEJAHATAN TERORGANISASI (ORGANIZED CRIME) PADA SEKTOR-SEKTOR EKONOMI, KEMANANAN HINGGA POLITIK - Fahmi, Teuku (JURNAL SOSIOLOGI, 2014)
This paper discusses the organized crime that has been threatened on a variety of important sectors in many countries, both sectors of the economy, politics and national security. Furthermore, this paper also presented growth opportunities identification and handling of organized crime in Indonesia.